Principle of a state governed by the rule of law in the Constitution of the Czech Republic (a few comments from the point of view of Poland’s experience) - Kruk, Maria (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The present considerations are devoted to the principle of a democratic state governed by the rule of law laid down in the Constitution of the Czech Republic of 1992: the way the principle is presented, its guarantees and protection that the Constitution provides for the essence of the state of law and the consequences of this regulation for both social and political life as well as for the development of the doctrine of constitutional law with respect to that issue. It is especially important that, apart from the declaration that the Czech Republic is a democratic state governed by the rule of law (Article 1 (1)), there is an additional reservation stipulating that any amendments violating this principle are impermissible (the eternity clause) and legal norms may not be interpreted in the way allowing such changes (Article 9 (2) and (3)). Moreover, other provisions of the Constitution connected with the principle are analysed, especially the rule that the majority decision-making shall take into consideration the interests of the minority (Article 6) and the citizens’ right to resist formulated expresis verbis (Article 23 Charter of Fundamental Rights and Freedoms).